Evaluasi Tempat Pemakaman Umum (TPU) di Kota Purwokerto, Kabupaten Banyumas - Rama Wahyu Prasetyo; Hercules Pungky Naga Dewa; Sutomo Sutomo (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2023)
This researcher evaluated the spatial layout of the Public Burial Place (TPU) in Purwokerto City, Banyumas Regency. With a focus on spatial aspects, this study uses a Geographic Information System (GIS) approach to analyze the suitability of burial grounds. The research method includes mapping and spatial analysis in the Purwokerto City area, which consists of four sub-districts and 27 kelurahan. In the analysis of burial ground suitability, important variables such as soil type, including inseptisol, entisol, and ultisol, are explored in detail. The results revealed that most areas in Purwokerto City have the potential to be used as burial grounds. GIS approach and spatial analysis help in identifying the most suitable areas for TPU development. This research provides valuable insights for spatial planning and burial ground management in the face of population growth challenges and land limitations.